A complete data set for the simulation of electron transport through gaseous tetrahydrofuran in the energy range 1–100 eV - García-Abenza, Adrián (2022)
PID2019-104727RB-C21 LINKA20085 DP180101655 PAPIIT-UNAM IN118520